An Unusual Presentation of Desmoplastic Small Round Cell Tumour of the Abdomen: Morphological, Immunohistochemical, Ultrastructural, and Molecular Studies - Preethika Angunawela; Alhossain A. Khalafallah; Karen Wolfswinkel; David Seaton; Terry Brain (Case Reports in Oncological Medicine)
Desmoplastic small round cell tumour (DSRCT) is an aggressive and a rare neoplasm. We report on a 34-year-old male who had abdominal discomfort with a large intraperitoneal mass. Histological examination of the tumour biopsy revealed sheets of small round cells. The cells were positive with vimentin and desmin (with occasional dot positivity) and negative for WT1 and CD 99 with immunohistochemistry. Cytogenetics showed a translocation disrupting the EWSR 1 gene on 22 q 12 consistent with DSRCT. Electron microscopic examination showed sparse cytoplasmic organelles. The patient succumbed 34 months from disease presentation after multiple chemotherapies and thereafter radiotherapy. In summary, our case exemplifies that it is crucial to combine clinical, histological, and molecular aspects in diagnosing DSRCT especially when characteristic dot positivity with desmin is weak along with deficient marking of WT1 and CD99 by immunohistochemistry. Histology was also less clear than published examples of this entity with a poor desmoplastic response. A multidisciplinary approach including early referral to specialised centres is recommended in these cases as tertiary referral centres will be required to substantiate the diagnosis.